Encyclopedia of communication and information - Schement, Jorge Reina (Gale virtual reference library, 2002)
Provides a comprehensive overview of universal modes of communication, the media used to communicate, theories of communication and their implications, careers in communications and information, and biographies of notable figures in the field. Organized for the general reader and designed to complement social studies, communications, and information systems curricula.